Utilization of social media in skill acquisition and entrepreneurial development among youths in Africa - Iwegbue. Ishioma N; Collins Kediehor (Journal of Management and Science, 2025)
Social media platforms have become powerful tools for developing entrepreneurial skills among youths in Africa. With the advent of technology and widespread internet access, these platforms have revolutionized communication and provided a platform for young entrepreneurs to showcase their talents, connect with potential customers, and acquire valuable business knowledge. Using the survey design, 8 - item questionnaire was used to generate data from 400 youths purposively selected to represent and reflect the opinions of youths present in Africa. The study revealed social media is an important tool in developing entrepreneurial skills in our society. It was discovered that young entrepreneurs prefers using Instagram for acquiring skills. The study also revealed that youths are exposed to social media to a large extent. The challenges youths encounter were Limited Access to reliable information, Difficulty in distinguishing information, lack of interaction and feedback, Information overload, Difficulty in distinguishing credible sources. Hence it was recommended that Experts should ensure they their entrepreneurial message are well designed for social media users or young entrepreneurs also social media platforms should be simple and flexible. In conclusion, social media has emerged as a crucial tool for developing entrepreneurial skills among youths. It enables young entrepreneurs to promote their businesses, connect with industry professionals, access valuable resources, and showcase their creativity. By leveraging these platforms effectively, aspiring entrepreneurs can enhance their business acumen, establish a strong brand presence, and contribute to the economic growth of Africa.